Pencantuman Klausul Arbitrase dalam Pengikatan Jual Beli Tanah - Anak Agung Bagus Ryan Ganandhika; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2022)
Arbitration is the settlement of civil disputes outside the court that bases arbitration clauses made in writing by the parties to the dispute. Arbitration clauses may be construed as individual provisions of an agreement on dispute resolution through arbitration. In resolving arbitration disputes requires the existence of arbitrators, the arbitrator is a private judge for the parties selected based on mutual agreement to resolve the dispute between them. The arbitrator who wishes to give a verdict fairly, honestly, and in accordance with the applicable provisions. The formulation of the issue discussed is how is the legal power against the phrase arbitration clause in the land buying and selling agreement ? and how is the mechanism of resolving land buying and selling disputes through arbitration ?. Research used using normative research types. Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution, dated August 12, 1999 which is intended to change the rules regarding arbitration institutions that are not in place with future developments. The establishment of a comprehensive arbitration clause is to pour out all the main elements contained in Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution.